METHODS AND CHALLENGES OF TRANSLATING ENGLISH PROVERBS AND IDIOMS FROM ENGLISH TO UZBEK (Ustozlar uchun, 2026)
This article explores the linguistic and cultural complexities involved in translating English proverbs and idioms into the Uzbek language. Unlike literal translation, rendering figurative language requires a deep understanding of the source culture and the application of specific translation strategies. The research focuses on practical analysis, categorizing translation methods into equivalent-based, analogical, and descriptive approaches. By examining specific examples, the article identifies major obstacles such as cultural untranslatability, lexical gaps, and stylistic differences. The findings emphasize that a successful translation must balance semantic accuracy with the preservation of the original’s emotional and aesthetic impact, often necessitating domestication or functional equivalence over direct word-for-word translation.